2009
DOI: 10.1111/j.1440-0960.2009.00518.x
|View full text |Cite
|
Sign up to set email alerts
|

Vulval and perianal inflammatory linear verrucous epidermal naevus

Abstract: Inflammatory linear verrucous epidermal naevus (ILVEN) is a rare form of epidermal naevus. It occurs as a linear dermatitic or psoriasiform plaque, with onset usually in the first 5 years of life. Lesions are characteristically intensely itchy. We present a case of ILVEN occurring on the vulva and perianal region of a 6-year-old girl. The lesion was initially thought to be an area of lichenified dermatitis; however, treatment with even super-potent topical corticosteroids did not significantly improve the infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…It presents as single or multiple erythematous, verrucous and characteristically pruritic plaques that follow Blaschko's lines and clearly stop at the median line (1). The lower extremities are typically affected (1), but a mucosal involvement has also been described (2).…”
Section: Introductionmentioning
confidence: 99%
“…It presents as single or multiple erythematous, verrucous and characteristically pruritic plaques that follow Blaschko's lines and clearly stop at the median line (1). The lower extremities are typically affected (1), but a mucosal involvement has also been described (2).…”
Section: Introductionmentioning
confidence: 99%
“…ILVEN most commonly occurs over the lower limb with a predilection for the left buttock. [12] Although literature search showed that inguino-genital presentation is very rare, both our cases presented with same. There have been further case reports of a 21-year-old male who had linear verrucous plaque over left side of body along with the involvement of penis and scrotum[3] and another male presenting with linear epidermolytic verrucous epidermal nevus over scrotum.…”
Section: Discussionmentioning
confidence: 72%
“…Clinically it presents as pruritic, verrucous, linear, plaque with an early age of onset and is resistant to treatment. [1] In half of the cases the onset is in the first 6 months of age[2] and almost all are present by the age of 4 years. [1] The ages of onset in our cases were at 5 years (Case 1) and at birth (Case 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient had satisfactory response to surgical excision. We report this interesting case as only few cases[5678910] are reported in the literature and also because, despite of having histopathological features of psoriasis, there was no response to antipsoriatic treatment but to surgical excision.…”
mentioning
confidence: 96%